Opposite Effects of Early-Life Competition and Developmental Telomere Attrition on Cognitive Biases in Juvenile European Starlings. - Melissa Bateson; Michael Emmerson; Gökçe Ergün; Pat Monaghan; Daniel Nettle (PLoS ONE)
Moods are enduring affective states that we hypothesise should be affected by an individual's developmental experience and its current somatic state. We tested whether early-life adversity, induced by manipulating brood size, subsequently altered juvenile European starlings' (Sturnus vulgaris) decisions in a judgment bias task designed to provide a cognitive measure of mood. We predicted that starlings from larger broods, specifically those that had experienced more nest competitors larger than themselves would exhibit reduced expectation of reward, indicative of a 'pessimistic', depression-like mood. We used a go/no-go task, in which 30 starlings were trained to probe a grey card disc associated with a palatable mealworm hidden underneath and avoid a different shade of grey card disc associated with a noxious quinine-injected mealworm hidden underneath. Birds' response latencies to the trained stimuli and also to novel, ambiguous stimuli intermediate between these were subsequently tested. Birds that had experienced greater competition in the nest were faster to probe trained stimuli, and it was therefore necessary to control statistically for this difference in subsequent analyses of the birds' responses to the ambiguous stimuli. As predicted, birds with more, larger nest competitors showed relatively longer latencies to probe ambiguous stimuli, suggesting reduced expectation of reward and a 'pessimistic', depression-like mood. However, birds with greater developmental telomere attrition--a measure of cellular aging associated with increased morbidity and reduced life-expectancy that we argue could be used as a measure of somatic state--showed shorter latencies to probe ambiguous stimuli. This would usually be interpreted as evidence for a more positive or 'optimistic' affective state. Thus, increased competition in the nest and poor current somatic state appear to have opposite effects on cognitive biases. Our results lead us to question whether increased expectation of reward when presented with ambiguous stimuli always indicates a more positive affective state. We discuss the possibility that birds in poor current somatic state may adopt a 'hungry' cognitive phenotype that could drive behaviour commonly interpreted as 'optimism' in food-rewarded cognitive bias tasks.